Kyrgyz Republic - Joint World Bank-IMF Debt Sustainability Analysis - World Bank (World Bank, Washington, DC, 2019)
The joint World Bank/IMF Debt Sustainability Analysis (DSA) has been prepared in the context of the 2019 Article IV Consultation, for the first time based on the revised framework for low-income countries. Results indicate moderate risk of debt distress for both external and overall public debt. However, the debt outlook remains vulnerable, especially to a deceleration in real GDP and exports growth and the depreciation of the KGS. To address these vulnerabilities, the authorities need to remain cautious when contracting and guaranteeing new debt, maintain fiscal discipline, improve public investment management, and continue improving the business environment to maintain the export potential of the country after the main gold mine will close in 2026.